2010
DOI: 10.1088/0960-1317/20/12/125023
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of a microplatform for the proximity effect study of localized ELF-EMF on the growth ofin vitroHeLa and PC-12 cells

Abstract: This paper presents a platform technology with experimental results that show the scientists and biologists a way to rapidly investigate and analyze the biological effects of localized extremely low frequency (ELF) electromagnetic field (EMF) on living cells. The proximity effect of the localized ELF-EMF on living cells is revealed using the bio-compatible microplatform on which an on-glass inductive coil array, the source of the localized ELF-EMF in micro scale, is designed, fabricated and operated with a fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…Indeed, a large number of studies have been carried out to investigate the effects of electromagnetic fields in biological systems [36][37][38][39][40][41][42][43][44][45][46][47][48][49]. Relevant in vitro studies can be summarized as:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a large number of studies have been carried out to investigate the effects of electromagnetic fields in biological systems [36][37][38][39][40][41][42][43][44][45][46][47][48][49]. Relevant in vitro studies can be summarized as:…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it has been reported that electromagnetic fields disturb the cancer cells' bioactivity, with a consequent abnormal cell signal transduction process, and that they change the ionic motion (K + , Na + , Ca 2+ and Cl − ) across the cell membrane. Indeed, the oscillating motion of ions near the cell membrane could exert significant voltage fluctuations in the voltage-gated channels leading to a disturbance in the signal transduction process and, consequently, to the inhibition of cell growth [41]. Moreover, several in vitro experiments have pointed out that a 1 h exposure to a 50 Hz, 22 mT magnetic field yields an increase in the intracellular Ca 2+ concentration [57,58], which in turn changes the endonuclease activity.…”
Section: Resultsmentioning
confidence: 99%
“…a) Human cervical cancer and rat pheochromocytoma cells show a 18.4% and 12.9% decrease, respectively, in cell proliferation when exposed continuously for 72 h to amagnetic field of 1.2 ± 0.1 mT, at 60 Hz [142]; b) Human cervical cancer cell proliferation decreased by 15% 24 h after being exposed to a magnetic field of 0.18 T, at 0.8 Hz, for 16 h [143]; c) Human colon adenocarcinoma cells decrease their growth when exposed to 1 Hz for 6 h [144]; and, in vivo: a) Exposure of nude mice bearing a subcutaneous human colon adenocarcinoma (WiDr), to 5.5 mT static magnetic fields for 70 min of exposure a day resulted in a significant increase of survival time, a significant inhibition of tumour growth, a reduction of cell proliferation and an increase of apoptosis in tumours of treated animals [145]; b) Male Fischer-344 rats, subjected to the modified resistant hepatocyte model exposed to 4.5 mT at 120 Hz electromagnetic and magnetic fields showed inhibition of preneoplastic lesions [146].…”
Section: An Example Of This Thermodynamic Standpoint: Biomedicine Engmentioning
confidence: 98%
“…Indeed, in order to live, cells need temperature differences in relation to their environments; for example, for Streptococcus faecalis it results around 0.4 °C · cm −1 [133]. As a consequence of the experimental results we can state that [133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148]: a) This temperature difference depends on the cell lines; b) For any cell line, this temperature difference depends on the cells' metabolism.…”
Section: An Example Of This Thermodynamic Standpoint: Biomedicine Engmentioning
confidence: 99%
“…Now, introducing the electro-chemical affinityà = A+Z φ related also to pH variation 14 and the electric field variation, with A j = Σ k ν kj µ j , Z the electric charge per unit mass, φ the electrostatic potential;15 and τ i , i ∈[1, 5], are the lifetimes of any process and:16 1. the chemical potential gradient can be approximated through the ratio between the mean value of the chemical potential 17 µ = 1.20 × 10 −9 J kg −1 and the mean density is considered as ρ = 1000 kg m −3 ;18 2. τ 1 is the time related to the thermal flow driven by temperature difference. It can be assessed considering that the time 19 constant of the thermal transient for heat conduction is τ cv ≈ ρcV /(hA) with ρ ≈ 1000 kg m −3 density, V the cell 20 volume, A the external cell surface, c ≈ 4186 J kg −1 K −1 specific heath, and h the convection heat transfer coefficient 21 evaluated as h ≈ 0.023Re 0.8 Pr 0.35 λ/L, where λ ≈ 0.6 W m −1 K −1 of heat conductibility, L the characteristic dimension 22 of the cell (here we have considered the diameter), Re ≈ 0.2 the Reynolds number and Pr ≈ 7 the Prandtl number.…”
mentioning
confidence: 99%